Solid alveolar rhabdomyosarcoma with multiple cutaneous site presentation in a child (Indian Journal of Case Reports, 2020)
Rhabdomyosarcomas (RMS) are the most common childhood soft-tissue tumors. Case reports of RMS presenting at multiple cutaneous sites simultaneously are extremely rare and most of these have been reported as of embryonal type which is the most common RMS in childhood. We present here a rare case of a 2-year-old child who presented to us with multiple cutaneous swellings that had grown over the past 6 months. Fine-needle aspiration cytology was performed from all the swellings and diagnosis of small round blue cell tumor was made. Biopsy from one of these swellings showed features of alveolar RMS (ARMS) (solid variant) that was confirmed on immunohistochemistry. ARMS are associated with a poorer prognosis compared to other RMS with higher rates of dissemination and mortality even after an initially good response to chemotherapy; hence, it becomes important to be aware of their unusual histological variants and accurately diagnose them.